THE POSITION OF WOMEN IN MALANG JAN’S POETRY - Waliullah Fazil; Jahan Zeb Ahmadi (CV. RADJA PUBLIKA, 2025)
Malang Jan, in his poetry, expresses feminine emotions through the voice of women in such a way that men are encouraged to fulfill their responsibilities, such as protecting the country, building it, promoting its development, achieving freedom, and more. When men do not have such feelings, women get up themselves and do these jobs. Malang Jan has shown the position of women in serving the country and feeling freedom as even higher than that of men. The reason might be that Malang Jan sees women as a valuable and responsible part of society. Also, he believes that women encourage men on the path of independence and service to the country. So far, a complete study and review have not been done on this part of Malang Jan’s poetry. Therefore, it was necessary to highlight this aspect in the content of his poems. This writing will introduce us, in an analytical way, to the expression of feminine emotions in Malang Jan’s poetry through folk language. The conclusion is that Malang Jan expressed his poetry in the voice of women because men quickly become emotional when reproached by women, show their reaction, and thus become ready for struggle and sacrifice. The method of this writing is explanatory-descriptive, and its style is documentary.